The dislocation movement in white tin single crystals - (:unkn) unknown (My University, 1996)
The ß-Sn single crystals used in this study were melted and grown by the modified Bridgman technique under a 10-4 torr vacuum, and oriented by the back-reflection Laue method. Single crystal plates were stretched in an etching solution produced hillocks at the sites of dislocations and trails of hillocks along the loci of moved dislocations. Two kinds of dislocation motion could be distinquished by the shapes of hillocks trails. The one corresponds to the movement of a dislocation which terminates at the surface, and the other, the movement of a dislocation which emerges by stressing from the interior.